Patient-reported outcomes from STARTRK-2: a global phase II basket study of entrectinib for ROS1 fusion-positive non-small-cell lung cancer and NTRK fusion-positive solid tumours - Paz-Ares, L. (ESMO Open, 2021)
BACKGROUND: Patient-reported outcomes (PROs) are increasingly relevant endpoints in clinical trials, contributing to our understanding of risk–benefit profiles, in addition to efficacy and safety data. We investigated the impact of entrectinib on patient-reported symptoms, functioning, and health-related quality of life. PATIENTS AND METHODS: STARTRK-2 is a phase II basket study in patients with locally advanced/metastatic neurotrophic receptor tyrosine kinase 1/2/3 (NTRK1/2/3) and ROS proto-oncogene 1 (ROS1) fusion-positive solid tumours. PROs (prespecified secondary endpoint) were evaluated using the European Organization for Research and Treatment of Cancer quality-of-life questionnaire (QLQ-C30), lung cancer module (QLQ-LC13), and colorectal cancer module (QLQ-CR29), and the EuroQoL 5-Dimension 3-Level instruments, completed before cycle 1 day 1 and each subsequent 4-week cycle of entrectinib dosing, and the end of treatment. Adverse events and treatment-related symptoms were assessed in the safety analysis (SA)-PRO population. Tumour-related symptoms, functioning, and global health status were assessed in the efficacy analysis (EA)-PRO population. Data cut-offs: 31 October 2018 NTRK cohort; 01 May 2019 ROS1 cohort. RESULTS: SA-PRO populations comprised patients with NTRK fusion-positive solid tumours (N = 88) or ROS1 fusion-positive non-small-cell lung cancer (N = 180) who received one or more doses of entrectinib, completed PRO questionnaires on cycle 1 day 1 and answered one or more questions on-study. EA-PRO populations (N = 71) and (N = 145), respectively, comprised SA-PRO patients with measurable baseline disease. Moderate-to-high baseline global health status scores were maintained in EA-PRO populations during treatment. Role and physical functioning scores were moderate-to-high at baseline, with trends towards clinical improvement during treatment. Both cohorts reported low-to-moderate symptom burden at baseline, which was maintained or trended towards clinically meaningful improvement. Symptoms commonly associated with cancer treatment (e.g. nausea, fatigue) remained stable or improved during treatment. All SA-PRO patients experienced one or more adverse events, most frequently constipation or diarrhoea. CONCLUSIONS: PRO findings were consistent with the favourable safety profile of entrectinib, and further reinforce the positive benefit–risk profile of this treatment, indicating minimal overall treatment burden.